Réponses

2014-03-28T21:15:10+01:00
Bonsoir,

A) 2x + 3 = 5
2x = 5 - 3
2x = 2
x = 2/2
x = 1

B) -3 +5x = 12 
5x + 12 + 3
5x = 15
x = 15/5
x = 3

C) 1 -2x = 1 
-2x = 1 - 1
-2x = 0
x = 0

D) -3x +3 = -x - 1
-3x + x = -1 - 3
-2x = -4
x = -4/(-2)
x = 2
2014-03-28T21:16:17+01:00
Salut :)

A) 2x + 3 = 5
2x = 5 - 3
2x = 2
x = 2/2
x = 1

B) -3 +5x = 12
5x = 12 + 3
5x = 15
x = 15/5
x = 3

C) 1 -2x = 1
-2x = 1 - 1
-2x = 0
x = 0/-2
x = 0

D) -3x +3 = -x-1

-3x + x + 3 = - 1
-2x = -1 - 3
-2x = -4
x = -4/-2
x = 2

J'espère t'avoir aidé(e)! :)